2016
DOI: 10.1016/j.gdata.2015.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India

Abstract: Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87 Mbps with 50.87% G + C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In this study, a high number of annotated features were classified as unknown function, suggesting the potential source of novel microbial species and their products. Similar results were found in the metagenome of Unkeshwar, another hot spring in India, where pathway annotation was done using KEGG (Mehetre et al, 2016 ). For each contig sequence, the assignment of KO numbers obtained from known reference hits was done, revealing up to 20% unclassified sequences.…”
Section: Functional Analysis Of Thermophilessupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, a high number of annotated features were classified as unknown function, suggesting the potential source of novel microbial species and their products. Similar results were found in the metagenome of Unkeshwar, another hot spring in India, where pathway annotation was done using KEGG (Mehetre et al, 2016 ). For each contig sequence, the assignment of KO numbers obtained from known reference hits was done, revealing up to 20% unclassified sequences.…”
Section: Functional Analysis Of Thermophilessupporting
confidence: 69%
“…The biodiversity of several hot environments such as oil reservoirs (Kotlar et al, 2011 ), compost (Martins et al, 2013 ), or hot springs (Zamora et al, 2015 ; Mehetre et al, 2016 ), was studied using shotgun metagenomics sequencing. Some of them are summarized in Table 2 .…”
Section: Diversity Analysis Of Thermophilesmentioning
confidence: 99%
“…NGS technologies have changed the approaches to both basic and applied research in plant virology. Due to the ability of NGS platforms to generate enormous data and their prompt delivery and cost-effectiveness, these techniques are becoming popular in various fields of biological research [ 120 , 121 ]. NGS-based techniques share a few familiar processes, such as the extraction of total nucleic acid (DNA or RNA) from the samples (environments, infected host plants, etc.…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Many studies have also revealed the presence of genes encoding for enzymes of biotechnological interest, such as hydrolases, xylanases, proteases, galactosidases, and lipases (Ferrandi et al, 2015; Littlechild, 2015). Some studies focusing on the metagenomic analysis of hot springs located in India have reported Bacillus licheniformis (Mangrola et al, 2015), Bacillus megaterium, Bacillus sporothermodurans, Hydrogenobacter sp., Thermus thermophilus, Thermus brockianus (Bhatia et al, 2015), Clostridium bifermentans, Clostridium lituseburense (Ghelani et al, 2015), Opitutus terrae, Rhodococcus erythropolis , and Cellovibrio mixtus (Mehetre et al, 2016) as major bacterial genera. Genes for stress responses and metabolism of aromatic and other organic compounds have been identified by preliminary functional analysis of these sites (Mangrola et al, 2015; Mehetre et al, 2016).…”
Section: Introductionmentioning
confidence: 99%